Solid waste composition and its management: A case study of Kirtipur Municipality-10 - Prakash Awasthi; Gopi Chataut; Ram Khatri (Heliyon, 2023)
The world population is expanding in line with the general trend. The demand for goods is currently higher than it has ever been before. This has resulted in the production of more waste than ever before. The problem of waste management is not new for humans but the complexity of the issue has increased more in present days. The research was focused on composition of solid waste and its management in Kirtipur-10. The research was conducted in ward 10 of Kirtipur municipality to know the ground reality of solid waste in households. The research aimed to understand the solid waste situation, its composition, problems and finding possible solutions to the problems. Household survey, Focused group discussion were conducted during November month of 2022 to collect data. 75 household were taken as sample for research. Wastes, collected from all of the groups of households, were segregated and weighed. Household solid waste (HSW) was comprised of seven categories of waste with organic waste being the largest component (44 %), plastic (13 %), paper (11 %), Glass (10 %), rubber (9 %), others (7 %) and Hazardous waste (6 %). Municipal authorities are usually the responsible agencies for solid waste collection and disposal, but the magnitude of the problem is well beyond the ability of any municipal government to tackle. There is strong dissatisfaction among municipal resident on waste management by local government. Looking at the composition of waste produced, composting of waste at home level can bring a sustainable solution to the problem. The solid waste management system in Kirtipur has low efficiency and needs to be improved.